Silica Aerogel Blanket
Patent Information
- Application Number
- JP2023121550
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-30
- Filing Date
- 2023-07-26
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2040-09-28
AI Technical Summary
【0022】 本発明によるシリカゾルは、触媒組成物に、塩基触媒、有機溶媒、疎水化剤および水を含み、この際、塩基触媒の含量を制御することで、シリカエアロゲルブランケットの製造時に、塩基触媒成分と多量の有機溶媒の存在下で行われて溶媒の使用量を増加させる湿潤熟成ステップと、多量の有機溶媒と高価の表面改質剤を使用し、工程が複雑で、長い工程時間を要して経済性および生産性を阻害する表面改質ステップを省略することができ、工程を単純化できるという効果がある。
Smart Images

Figure 0007638336000001 
Figure 0007638336000002
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority to Korean Patent Application No. 10-2019-0121123 filed on September 30, 2019, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a method for producing a silica aerogel blanket having excellent hydrophobicity by using a silica sol containing a hydrophobizing agent and water in a catalyst composition, and the method can simplify the manufacturing process of the aerogel blanket and increase the efficiency of reuse of waste liquid generated after the manufacturing process. [Background technology]
[0003] Aerogel is a super-porous material with a porosity of 90-99.9% and a pore size of 1-100 nm, and a high specific surface area (≧500 m 2 Aerogel is a material that has excellent properties such as being extremely lightweight, extremely insulating, and extremely low dielectric constant. Needless to say, research and development into aerogel materials is being conducted, but research into its applications as an environmentally friendly high-temperature insulating material, extremely low dielectric thin film for highly integrated devices, catalysts and catalyst supports, electrodes for supercapacitors, and electrode materials for seawater desalination is also being actively conducted.
[0004] The greatest advantage of aerogel is that it has super-insulation properties, exhibiting a thermal conductivity of less than 0.300 W / mK, which is lower than conventional organic insulation materials such as styrofoam, and that it solves the fatal weaknesses of organic insulation materials, namely, vulnerability to fire and the generation of harmful gases during a fire.
[0005] Generally, aerogels are produced by producing hydrogels from silica precursors such as water glass or alkoxysilanes (TEOS, TMOS, MTMS, etc.) and then removing the liquid components inside the hydrogel without destroying the microstructure.
[0006] In particular, hydrophobic silica aerogel blankets, in which hydrophobic silica aerogel is formed on fibers, are widely used in construction and industrial sites as functional heat insulating materials that prevent corrosion caused by moisture, and such hydrophobic silica aerogel blankets are generally manufactured through the steps of preparing a silica sol solution, gelling, aging, surface modification, and drying.
[0007] However, among the conventional manufacturing methods, the surface modification step requires a large amount of organic solvent and an expensive surface modifier, and is complicated and requires a long process time, resulting in poor economic efficiency and productivity, and the ammonia generated by modifying the surface of the silica aerogel with the surface modifier reacts with carbon dioxide used in the supercritical step to form ammonium carbonate salt, which causes problems such as clogging the piping of the supercritical drying equipment and impairing the efficiency of the process. In addition, a large amount of ammonia is present in the waste liquid generated after drying, making it impossible to immediately reuse the waste liquid, and in order to reuse the waste liquid, a purification process takes a long time, which increases the purification cost.
[0008] In addition, the aging step, which is a step for strengthening the structure of aerogel, exhibits a structural strengthening effect when wet aging is performed in the presence of a base catalyst solution such as ammonia / ethanol. However, wet aging generates residual ammonia, which causes the same problems as those caused by surface modification during drying and when the waste liquid is reused, and there is also a problem of increased costs due to the need to use additional solvents.
[0009] In addition, after gelation, a wet aging step and a surface modification step must be performed, which causes inconvenience due to the complicated process.
[0010] Therefore, the inventors of the present invention have conducted extensive research into a method for producing a silica aerogel blanket with a strong structure that exhibits hydrophobicity without the need for wet aging, and have developed a method for producing a silica aerogel blanket that can solve the problems associated with the conventional wet aging and surface modification steps. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Korean Patent No. 10-1147494 Summary of the Invention [Problem to be solved by the invention]
[0012] The present invention has been made to solve the problems of the prior art. The problem to be solved by the present invention is to provide a silica sol that can omit a wet aging step, which is performed in the presence of a base catalyst and an organic solvent and increases the amount of solvent used, and a surface modification step, which uses a large amount of an organic solvent and an expensive surface modifier, making the process complicated and requiring a long process time, thereby hindering economy and productivity, and a method for manufacturing a silica aerogel blanket using the same.
[0013] The present invention provides a silica sol that can reduce energy consumption by omitting the wet aging step and surface modification step that can be performed at high temperatures, and can use simplified manufacturing equipment because omitting the steps makes it unnecessary to use an aging solution supply equipment and a surface modification supply equipment, and a method for manufacturing a silica aerogel blanket using the same.
[0014] Another problem to be solved by the present invention is to provide a silica sol that can significantly suppress the generation of ammonium carbonate salt during supercritical drying by the ammonia remaining after use in wet aging and the ammonia generated when the surface of the silica aerogel blanket is modified by a surface modifier, and a method for manufacturing a silica aerogel blanket using the same.
[0015] Still another problem to be solved by the present invention is to provide a method for producing a silica aerogel blanket, which can reduce the amount of ammonia remaining in the waste liquid after drying, thereby enabling efficient reuse of the waste liquid, improving the reuse rate of the waste liquid, and reducing the loss of the solvent and hydrophobizing agent.
[0016] Yet another problem to be solved by the present invention is to provide a method for producing a silica aerogel blanket in which the gelation time can be easily adjusted by adjusting the amount of a base catalyst in the catalyst composition.
[0017] Still another problem to be solved by the present invention is to provide a silica aerogel blanket having an excellent degree of hydrophobicity inside the blanket and an excellent cross-sectional water repellency of the blanket. [Means for solving the problem]
[0018] In order to achieve the above-mentioned object, according to one embodiment of the present invention, the present invention is for solving the above-mentioned problems, and provides a silica sol comprising a silica precursor composition and a catalyst composition, the catalyst composition comprising a hydrophobizing agent, a base catalyst, water and an organic solvent, and the base catalyst is contained in an amount of 0.4 to 1.0 parts by weight per 100 parts by weight of the silica sol.
[0019] The present invention also provides a silica sol in which the catalyst composition contains 3 to 8 equivalents of water per equivalent of a hydrophobizing agent.
[0020] According to another embodiment of the present invention, there is provided a method for producing a silica aerogel blanket, the method including the steps of: 1) preparing a silica sol; 2) impregnating a blanket substrate with the silica sol; and 3) allowing the silica sol-blanket substrate composite to stand, wherein the silica sol is the silica sol described above.
[0021] According to another embodiment of the present invention, there is provided a silica aerogel blanket including a blanket substrate and silica aerogel formed inside and on a surface of the blanket substrate, the silica aerogel blanket having a cross-sectional water repellency of 0 wt% to 7 wt%. Effect of the Invention
[0022] The silica sol according to the present invention includes a catalyst composition including a base catalyst, an organic solvent, a hydrophobizing agent, and water. In this case, by controlling the content of the base catalyst, the wet aging step, which is performed in the presence of a base catalyst component and a large amount of an organic solvent and increases the amount of solvent used, and the surface modification step, which uses a large amount of an organic solvent and an expensive surface modifier, is complicated and requires a long process time, thereby hindering economy and productivity, can be omitted during the preparation of the silica aerogel blanket, thereby simplifying the process.
[0023] The present invention can reduce energy consumption by omitting the wet aging step and the surface modification step, which can be performed at high temperatures. By omitting the steps, aging solution supply equipment and surface modification supply equipment are not required, so simplified manufacturing equipment can be used.
[0024] In addition, the method for producing a silica aerogel blanket according to the present invention does not require wet aging in the presence of a base catalyst solution, and instead allows dry aging in a step of leaving the blanket without a solvent, which has the effect of reducing the amount of solvent used. The amount of ammonia generated by the surface modification of the silica aerogel blanket due to the ammonia and surface modifier remaining after use in the aging step can be significantly reduced, and ammonium carbonate generated during supercritical drying can be significantly suppressed.
[0025] In addition, since the amount of ammonia in the waste liquid can be significantly reduced, the waste liquid can be reused efficiently, and as the reuse rate of the waste liquid improves, the amount of loss of the solvent and the hydrophobizing agent can be reduced.
[0026] In addition, the present invention has an effect that the gelation time can be easily adjusted by adjusting the amount of the base catalyst in the catalyst composition, the hydrophobicity of the inside of the produced silica aerogel blanket is excellent, and the cross-sectional water repellency of the blanket is excellent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] The present invention will be described in detail below with reference to the drawings. The terms and words used in the present specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as meanings and concepts that are consistent with the technical ideas of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.
[0028] Silica aerogel blankets are widely used as heat insulating materials in construction and industrial sites. If the surface is not hydrophobized, the silanol groups (Si-OH) on the silica surface are hydrophilic, and the thermal conductivity gradually increases as the silanol groups absorb water from the air. In addition, the pores are severely collapsed during the drying process, making it difficult to expect the spring back phenomenon, and it is difficult to manufacture super heat insulating products with mesopores.
[0029] Therefore, in order to suppress absorption of moisture from the air and maintain low thermal conductivity, a step of modifying the surface of silica aerogel to make it hydrophobic is essential.
[0030] However, the surface modification step for hydrophobicity requires the use of a large amount of organic solvent and an expensive hydrophobizing agent, and requires a process for recovering and separating by-products generated in the surface modification step, which makes the aerogel manufacturing process complicated and uneconomical in terms of time and cost, thereby hindering the commercialization of silica aerogel blankets.
[0031] Therefore, the present invention provides a silica sol that makes it possible to omit the aging step and the surface modification step in the manufacture of a silica aerogel blanket in order to save process time and cost, reduce the generation of salts that cause problems in drying equipment during supercritical drying, and increase productivity by efficiently reusing waste liquid, a silica aerogel blanket manufactured using the same, and a manufacturing method thereof.
[0032] 1. Silica sol The silica sol according to one embodiment of the present invention includes a silica precursor composition and a catalyst composition, the catalyst composition includes a hydrophobizing agent, a base catalyst, water and an organic solvent, and the base catalyst is included in an amount of 0.4 to 1.0 parts by weight per 100 parts by weight of the silica sol. Here, the silica sol may be a precursor that can finally produce silica aerogel by gelation reaction, or may be produced by mixing the silica precursor composition and the catalyst composition.
[0033] Hereinafter, the silica precursor composition and the catalyst composition will be described separately.
[0034] (Silica Precursor Composition) A silica precursor composition according to one embodiment of the present invention may include a silica precursor, an organic solvent, and water.
[0035] In this case, the silica precursor contained in the silica precursor composition is a material that allows the produced aerogel to contain silica, and examples thereof include tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), methyl triethyl orthosilicate, dimethyl diethyl orthosilicate, tetrapropyl orthosilicate, tetraisopropyl orthosilicate, tetrabutyl orthosilicate, tetra secondarybutyl orthosilicate, tetra tertiarybutyl orthosilicate, tetrahexyl orthosilicate, tetraisopropyl ... One or more selected from the group consisting of tetracyclohexyl orthosilicate, tetracyclohexyl orthosilicate, and tetradodecyl orthosilicate can be used, and prehydrolysates of the above compounds can also be used. When using the prehydrolysates, the addition of acid is not necessary, the hydrolysis step of the silica precursor can be shortened or omitted, and the surface modification effect can be promoted.
[0036] More specifically, in the present invention, the silica precursor (HTEOS) can be prehydrolyzed polyethylsilicate.
[0037] Here, HTEOS is a prehydrolyzed ethyl polysilicate oligomer material having a wide molecular weight distribution, and when synthesizing TEOS monomer into an oligomer form by varying the degree of prehydrolysis (hydration degree), physical properties such as gelation time can be adjusted, and it can be easily applied according to the user's reaction conditions. In addition, it has the advantage of forming reproducible physical properties of the final result.
[0038] The silica precursor may be used in an amount that allows the silica content in the silica sol to be 0.1% by weight to 30% by weight, but is not limited thereto. When the silica content satisfies the above range, it is preferable in terms of ensuring an excellent level of mechanical properties, especially flexibility, of the aerogel blanket and improving the heat insulating effect.
[0039] Specifically, the organic solvent may be an alcohol, and the alcohol may be a monohydric alcohol such as methanol, ethanol, isopropanol, butanol, or a polyhydric alcohol such as glycerol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, and sorbitol, and any one or a mixture of two or more of these may be used. Among them, in consideration of miscibility with water and aerogel, a monohydric alcohol having 1 to 6 carbon atoms such as methanol, ethanol, isopropanol, butanol, for example, ethanol, may be used. The alcohol (organic solvent) and water as described above can be used in an appropriate amount by a person skilled in the art, taking into consideration the degree of hydrophobicity in the aerogel to be finally produced, while promoting the surface modification reaction.
[0040] (Catalyst composition) The catalyst composition according to one embodiment of the present invention includes a hydrophobizing agent, a base catalyst, water, and an organic solvent, and is characterized in that the base catalyst is included in an amount of 0.4 to 1.0 parts by weight based on 100 parts by weight of silica sol.
[0041] The catalyst composition of the present invention contains water together with the hydrophobizing agent in the composition, so that the hydrophobizing agent contained in the catalyst composition can be activated, and as the hydrophobizing agent is activated, aging and surface modification can be performed without using a separate aging solution and surface modification solution. Here, the activation of the hydrophobizing agent can mean that a hydrolysis reaction is performed on a functional group other than the alkyl group of the hydrophobizing agent, such as an alkoxy group or a halogen group, to form a hydroxyl group (-OH) at the position of the functional group. When the hydrophobizing agent is activated, the reactivity with the -Si-O- functional group forming the network structure in the silica wet gel can be significantly increased, and the hydrophobizing agent and the silica wet gel can react without a separate additional catalyst and solvent, thereby strengthening the structure and modifying the surface.
[0042] If the catalyst composition contains a hydrophobizing agent but does not contain water, the hydrophobizing agent cannot be activated, and therefore, for subsequent aging and surface modification, aging and surface modification processes that require a large amount of solvent under high temperature conditions must be performed as in conventional methods, and a problem may occur in that the surface modification reaction does not occur when dry aging is performed. Therefore, the structure is not strengthened, and the gel structure may shrink during drying, resulting in a problem in that a hydrophobic silica aerogel blanket cannot be manufactured due to the absence of a surface modification reaction.
[0043] If the hydrophobizing agent is included in the silica precursor composition rather than the catalyst composition, the gelation time may vary over time after the silica precursor is produced, which may cause a problem that it is difficult to apply it to a continuous aerogel blanket production process. For example, when a roll-shaped silica aerogel blanket is produced using a roll-to-roll technique, the raw materials may be stored in a state in which the silica precursor composition and the catalyst composition are stored in a storage tank, and the composition may be sprayed onto a blanket substrate on a conveyer belt and gelation may be performed while the conveyer belt is moving. In this case, if the gelation time varies depending on the residence time of the silica precursor composition in the storage tank, there may be a problem that the gelation is not partially performed in the produced wet gel blanket. Even when the conveyer belt for gelation is completely moved and the wet gel blanket is wound into a roll, there may be a part that is not gelled, which may cause a problem that it is difficult to produce a normal aerogel blanket. In addition, since the surface of the produced wet gel blanket is not modified during dry aging, a shrinkage phenomenon may occur during drying, which may cause a problem that a hydrophobic aerogel blanket cannot be formed.
[0044] According to one embodiment of the present invention, an alkylsilane compound is used as a hydrophobizing agent, and the hydrophobizing agent can participate in the gelation reaction as a co-precursor, thereby hydrophobizing the formed silica wet gel blanket. The alkylsilane compound gels together with the silica precursor in the gelation step, and the alkylsilane compound enclosed in the gel undergoes maturation and surface modification in the leaving step to form an alkyl-Si-O-Si network to hydrophobize the silica wet gel blanket, so that the surface modification step can be omitted when manufacturing a hydrophobic silica aerogel blanket. As a result, the amount of organic solvent and surface modifier used in the surface modification step can be reduced, and the process time and manufacturing costs can be reduced. In addition, the amount of ammonia generated by the surface modification of the silica wet gel can be significantly reduced, and the reuse efficiency of the waste liquid generated after the manufacture of the silica aerogel blanket can be increased, and the amount of hydrophobizing agent used can be significantly reduced even when the waste liquid is reused, because the hydrophobizing agent component contained in the waste liquid can also be contained in the silica sol when the waste liquid is reused.
[0045] Here, the hydrophobizing agent may be, specifically, an alkylsilane compound as described above, and the type is not limited as long as it is an alkylsilane compound containing an alkyl group that induces hydrophobization and a silane functional group that can react with the -Si-O- functional group of the wet gel. More specifically, the hydrophobizing agent may include one or more selected from the group consisting of trimethylethoxysilane (TMES), trimethylsilanol (TMS), trimethylchlorosilane (TMCS), methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), dimethyldiethoxysilane (DMDEOS), ethyltriethoxysilane, and phenyltriethoxysilane.
[0046] Also, according to one embodiment of the present invention, it is more preferable that the hydrophobizing agent does not include a silazane-based compound such as hexamethyldisilazane. If the hydrophobizing agent includes a silazane-based compound, the silazane-based compound may begin to decompose when it comes into contact with an organic solvent, generating ammonia, and when the hydrophobizing agent is added to a catalyst composition containing an organic solvent, a high pH is formed due to the generation of ammonia, and a gelation reaction may occur immediately. Therefore, in order to prevent unexpected gelation reactions and to easily adjust the gelation time by changing the amount of catalyst, it is preferable that the hydrophobizing agent does not include a silazane-based compound.
[0047] The hydrophobizing agent can be contained in an amount of 3 to 15 parts by weight, specifically 5 to 10 parts by weight, more specifically 6 to 8 parts by weight, based on 100 parts by weight of silica sol. Within the above range, the hydrophobizing efficiency (surface modification efficiency) can be further improved compared to the amount used.
[0048] Furthermore, the catalyst composition according to one embodiment of the present invention may contain 1 to 12 equivalents of water relative to 1 equivalent of the hydrophobizing agent.
[0049] Specifically, the water can be contained in an amount of 1 to 12 equivalents, 2 to 10 equivalents, 3 to 8 equivalents, 4 to 8 equivalents, and more preferably 5 to 6 equivalents relative to 1 equivalent of the hydrophobizing agent.
[0050] When the water is contained in an amount of 3 or more equivalents relative to 1 equivalent of the hydrophobizing agent, the hydrophobizing agent can be sufficiently activated, and the structure and surface modification of the wet gel can be easily performed without additional catalysts, surface modifiers, and solvents, and thus a silica aerogel blanket with excellent hydrophobicity can be produced without wet aging and another surface modification process that requires high temperature conditions and a large amount of organic solvent and surface modifier. Also, when the water is contained in an amount of 8 or less equivalents relative to 1 equivalent of the hydrophobizing agent, the amount of water in the wet gel blanket can be controlled, and thus the water can be effectively removed during the supercritical drying process, the shrinkage of the aerogel due to water can be suppressed, and the thermal conductivity and hydrophobicity can be further improved.
[0051] In addition, the base catalyst may be included in an amount of 0.4 to 1.0 parts by weight, specifically 0.6 to 1.0 parts by weight, more specifically 0.6 to 0.8 parts by weight, based on 100 parts by weight of the catalyst composition and 100 parts by weight of the total silica sol. If the base catalyst is included in an amount of less than 0.4 parts by weight, the reactivity between the hydrophobizing agent and the silica gel surface may be weak during the leaving process of step 3), and the surface may not be modified. If the base catalyst is included in an amount of more than 1.0 parts by weight, the gelation speed may be too fast, making it difficult to produce a uniform gel, and the physical properties may be reduced due to the formation of a non-uniform gel.
[0052] The base catalyst according to one embodiment of the present invention can be any substance that can create a pH condition for gelation, and examples of the base catalyst include inorganic bases such as sodium hydroxide and potassium hydroxide; and organic bases such as ammonium hydroxide.
[0053] Specifically, the organic base may be ammonium hydroxide (NH4OH), tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH), methylamine, ethylamine, isopropylamine, monoisopropylamine, diethylamine, diisopropylamine, dibutylamine, trimethylamine, triethylamine, triisopropylamine, tributylamine, choline, monoethanolamine, diethanolamine, 2-aminoethanol, 2-(ethylamino)ethanol, 2-(methylamino)ethanol, n-methyldiethanolamine, dimethylaminoethanol, diethylaminoethanol, nitrilotriethanol, 2-(2-aminoethoxy)ethanol, 1-amino-2-propanol, triethanolamine, monopropanolamine, or dibutanolamine, or a mixture of two or more may be used. More specifically, the base catalyst may be ammonium hydroxide (aqueous ammonia; NH4OH).
[0054] In addition, the organic solvent according to one embodiment of the present invention is as described above, and the amount of the organic solvent used can be appropriately adjusted in consideration of compatibility with water and wet gel, structural reinforcement, and ease of surface modification.
[0055] The catalyst composition may be contained in an amount that allows the pH of the silica sol to be 4 to 8. When the pH of the silica sol is contained within the above range, gelation can be easily and efficiently performed. In addition, the catalyst composition is added in the form of a solution in which the base catalyst is diluted in water and an organic solvent, so that the problem of catalyst precipitation can be prevented.
[0056] 2. Manufacturing method of silica aerogel blanket Specifically, a method for producing a hydrophobic silica aerogel according to an embodiment of the present invention includes the steps of 1) preparing a silica sol, 2) impregnating a blanket substrate with the silica sol, and 3) allowing the silica sol-blanket substrate composite to stand, and the silica sol is the silica sol described above.
[0057] Hereinafter, each step of the method for producing the hydrophobic silica aerogel of the present invention will be described in detail.
[0058] Step 1) Step 1) according to one embodiment of the present invention is a step of preparing a silica sol, which may be performed by mixing a silica precursor composition and a catalyst composition, wherein the silica sol, the silica precursor composition and the catalyst composition are all as described above.
[0059] In addition, the silica precursor composition and the catalyst composition may be mixed at room temperature and pressure.
[0060] The present invention is characterized in that by preparing the above-mentioned silica sol in step 1), gelation, structural reinforcement and surface modification can be achieved even if the silica sol-blanket substrate composite is left standing without an additional base catalyst, surface modifier and organic solvent in step 3) described below.
[0061] Step 2) Step 2) according to one embodiment of the present invention is a step of forming a silica sol-blanket substrate composite, which can be carried out by impregnating the silica sol of step 1) into the blanket substrate.
[0062] The term "impregnation" as used herein refers to the introduction of a flowable sol into the blanket substrate, and can refer to the penetration of the sol into the internal pores of the blanket substrate.
[0063] The blanket substrate according to an embodiment of the present invention may be a porous substrate in order to improve the thermal insulation of the silica aerogel blanket. When a porous blanket substrate is used, the silica sol can easily penetrate into the substrate, and aerogel can be uniformly formed inside the blanket substrate, so that the manufactured silica aerogel blanket can have excellent thermal insulation.
[0064] According to one embodiment of the present invention, the blanket substrate may be a film, a sheet, a net, a fiber, a porous body, a foam, a nonwoven fabric, or a laminate of two or more layers thereof. In addition, the surface of the blanket substrate may be roughened or patterned depending on the application. Specifically, the blanket substrate may be a fiber that can further improve the insulation performance by including spaces or voids in the blanket substrate that facilitate the formation of aerogel, and a material having low thermal conductivity may be used.
[0065] Specifically, the blanket substrate may be polyamide, polybenzimidazole, polyaramid, acrylic resin, phenolic resin, polyester, polyetheretherketone (PEEK), polyolefin (such as polyethylene, polypropylene, or copolymers thereof), cellulose, carbon, cotton, wool, hemp, nonwoven fabric, glass fiber, or ceramic wool.
[0066] Step 3) Step 3) according to one embodiment of the present invention is a step of leaving the silica sol-blanket substrate composite, during which gelation, aging and surface modification can occur.
[0067] Furthermore, the present invention is characterized in that by using the silica sol of step 1) described above, aging and surface modification can be easily performed after gelation without using a separate surface modification solution and aging solution (base catalyst and solvent).
[0068] In this way, since the surface modification process using wet aging and a separate surface modification solution is not performed, the amount of solvent and surface modifier used can be significantly reduced compared to the conventional silica aerogel blanket manufacturing process. In addition, the amount of base catalyst component contained in wet aging and the amount of ammonia generated in the surface modification reaction can be significantly reduced, and the amount of ammonia in the waste liquid generated after the aerogel blanket manufacturing process can be reduced, thereby increasing the reuse efficiency of the waste liquid.
[0069] According to one embodiment of the present invention, the step 3) may be performed under a temperature condition of room temperature or above room temperature. Here, the room temperature may specifically indicate a temperature of 15°C to 30°C, 15°C to 25°C, or 20°C to 25°C. The temperature above room temperature may mean a high-temperature condition that exceeds the room temperature and may cause gelation, aging, and surface modification of the silica sol-blanket substrate composite, and specifically may indicate a temperature of 30°C to 100°C, 40°C to 80°C, or 50°C to 70°C.
[0070] Furthermore, when step 3) is performed at room temperature, step 3) may be performed for 5 hours to 48 hours, preferably 10 hours to 38 hours, and more preferably 15 hours to 24 hours. When step 3) is performed under a temperature condition above room temperature, step 3) may be performed for 1 hour to 24 hours, preferably 2 hours to 15 hours, and more preferably 3 hours to 10 hours.
[0071] That is, the step 3) may be performed under room temperature or over room temperature conditions, which can perform gelation, aging, and surface modification of the silica sol-substrate composite for blanket, and the performing time may be adjusted according to the temperature conditions. As a specific example, when performing the step 3) on the same silica sol-substrate composite for blanket, the temperature conditions may be selected from room temperature conditions and over room temperature conditions. In this case, when performing the step under room temperature conditions, it may take a longer time than when performing the step under over room temperature conditions, but it is possible to reduce energy costs because no heat energy is required to maintain the temperature over room temperature. In addition, when performing the step under over room temperature conditions, it may consume more heat energy to maintain the temperature over room temperature than when performing the step under room temperature conditions, but it is possible to reduce the performing time of the step 3). Therefore, the temperature conditions of the step 3) may be appropriately selected as necessary, and it is preferable to perform the step under room temperature conditions in terms of reducing heat energy to maintain the temperature over room temperature.
[0072] In addition, the production method of the present invention can easily adjust the gelation time by adjusting the amount of the base catalyst in the catalyst composition, thereby producing a silica aerogel with the intended physical properties. In this case, the preferred gelation time can be adjusted to 1 to 25 minutes, specifically 5 to 10 minutes.
[0073] In the present invention, gelation may refer to the formation of a network structure from a precursor material, and the network structure may refer to a planar network-shaped structure in which certain polygons having one or more types of atomic arrangements are linked together, or a structure in which vertices, corners, faces, etc. of certain polyhedra are shared to form a three-dimensional skeletal structure.
[0074] In addition, according to an embodiment of the present invention, after the step 3), a drying step can be further included, and the silica wet gel blanket can be dried to prepare a hydrophobic silica aerogel.
[0075] Meanwhile, the method according to an embodiment of the present invention may further include a washing step before the drying step. The washing step is for removing impurities (sodium ions, unreacted materials, by-products, etc.) generated during the reaction and residual ammonia that may react with CO2 to generate ammonium carbonate during supercritical drying, to obtain a high-purity hydrophobic silica aerogel, and may be performed by a dilution process or an exchange process using a non-polar organic solvent.
[0076] The drying step according to an embodiment of the present invention may be performed by removing the solvent while maintaining the pore structure of the aged silica gel, and may be performed by supercritical drying.
[0077] The supercritical drying process can be carried out using supercritical carbon dioxide. Carbon dioxide (CO2) is in a gaseous state at room temperature and pressure, but when it exceeds a certain temperature and pressure limit called the supercritical point, it enters a critical state where the evaporation process does not occur and it is indistinguishable between gas and liquid. Carbon dioxide in this critical state is called supercritical carbon dioxide.
[0078] Supercritical carbon dioxide has a molecular density close to that of a liquid, but a low viscosity that is close to that of a gas. It has fast diffusion and high thermal conductivity, which makes it highly efficient at drying and shortens the drying process time.
[0079] Specifically, the supercritical drying process involves placing the aged silica gel in a supercritical drying reactor, filling it with liquid CO2, and then performing a solvent replacement process in which the alcohol solvent inside the silica aerogel is replaced with CO2. Thereafter, the temperature is raised to 40°C to 80°C at a predetermined heating rate, specifically at a rate of 0.1°C / min to 1°C / min, and then a pressure equal to or higher than the pressure at which carbon dioxide becomes supercritical, specifically at a pressure of 100 bar to 170 bar, is maintained, and the carbon dioxide supercritical state is maintained for a predetermined time, specifically 20 minutes to 1 hour. Generally, carbon dioxide becomes supercritical at a temperature of 31°C and a pressure of 73.8 bar. After maintaining the predetermined temperature and pressure at which carbon dioxide becomes supercritical for 2 hours to 12 hours, more specifically 2 hours to 6 hours, the pressure is gradually removed to complete the supercritical drying process and produce an aerogel blanket.
[0080] As a result of the drying process, a porous silica aerogel having nano-sized pores and / or a blanket containing the porous silica aerogel can be produced. The silica aerogel has a high degree of hydrophobicity and excellent physical properties, particularly low tap density and high porosity, and the silica aerogel-containing blanket containing the same has low thermal conductivity and excellent mechanical flexibility.
[0081] In addition, before or after the drying process, a pressing process for adjusting the thickness and making the internal structure and surface shape of the blanket uniform, a molding process for providing an appropriate shape or morphology depending on the application, or a lamination process for laminating another functional layer may be further performed.
[0082] 3. Silica Aerogel Blanket The present invention provides an aerogel blanket having uniform thermal conductivity and significantly improved overall thermal insulation due to the formation of uniform thermal conductivity within the blanket. According to one embodiment of the present invention, the present invention provides a silica aerogel blanket including a blanket substrate and silica aerogel formed inside and on the surface of the blanket substrate, and having a cross-sectional water repellency of 0.0wt% to 7.0wt% and excellent hydrophobicity within the blanket. Specifically, the silica aerogel blanket can have a large amount of aerogel particles uniformly formed inside and on the surface of the blanket.
[0083] Specifically, the cross-sectional water repellency may be 2.5 wt% or less, or 2.0 wt% or less, or 0.0 wt% or more, or 0.1 wt% or more. A low cross-sectional water repellency indicates that the silica aerogel in the blanket substrate is uniformly formed, and a cross-sectional water repellency of 0 wt% means that no moisture has penetrated into the cross-section of the silica aerogel blanket.
[0084] The silica aerogel blanket can be manufactured by the above-mentioned method for manufacturing a silica aerogel blanket.
[0085] The thickness of the silica aerogel blanket can be appropriately selected by adjusting the thickness of the blanket substrate depending on the application. In consideration of ease of handling and storage in a roll form, the thickness may be specifically 20 mm or less, more specifically 0.1 to 20 mm.
[0086] Here, the cross-sectional water repellency may be the water repellency measured after cutting the manufactured silica aerogel blanket with a thickness of 10 mm in the thickness direction, specifically, the water repellency may be the water repellency measured by cutting a silica aerogel blanket test piece with a size of 10 mm x 100 mm x 10 mm in the thickness direction. The water repellency may also be measured by the following measurement method. The test piece is floated on distilled water at 21 ± 2 ° C., and the mesh screen on the test piece is submerged to 127 mm below the water surface. After 15 minutes, the screen is removed, and when the test piece floats up, the test piece is clamped with a clamp and hung vertically for 60 ± 5 seconds. Next, the weight before and after impregnation is measured to confirm the weight increase rate, which can be expressed as the water repellency.
[0087] As a result, the aerogel blanket of the present invention can be usefully used as a heat insulating material, heat retaining material, or non-combustible material for aircraft, ships, automobiles, building structures, etc., as well as for heat and cold insulation plant facilities such as piping in various industrial facilities and industrial furnaces. EXAMPLES
[0088] In order to facilitate understanding of the present invention, the present invention will be described in detail with reference to the following examples. However, the examples according to the present invention may be modified in various different forms, and the scope of the present invention should not be construed as being limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those having average knowledge in the field to which the present invention belongs.
[0089] Example 1 A silica precursor composition was prepared by adding 31.90 g of prehydrolyzed TEOS (silica content = 20 wt%, HTEOS), 31.35 g of ethanol, and 2.8 g of water to a reactor and mixing them. In addition, a catalyst composition was prepared by adding 7.77 g of trimethylethoxysilane (TMES) as a hydrophobizing agent, 47.28 g of ethanol, 4.22 g of water, and 2.75 g of ammonia water (concentration: 30 wt%) as a base catalyst to another reactor and mixing them. In this case, the amount of water in the prepared catalyst composition was 5.12 equivalents per 1 equivalent of TMES, and the amount of base catalyst was 0.64 parts by weight per 100 parts by weight of the total sol. The prepared silica precursor composition and catalyst composition were mixed to prepare a silica sol, and the silica sol was impregnated into a fiber (glass fiber mat, 10 mm) as a blanket substrate. The fiber composite impregnated with silica sol was left at room temperature for 24 hours to undergo gelation, surface modification, and aging. The produced silica wet gel blanket was placed in a 7.2L supercritical extractor and CO2 was injected. Next, the temperature inside the extractor was raised to 70°C for 1 hour and 20 minutes, and when it reached 70°C and 150 bar, CO2 was injected and discharged at a rate of 0.5L / min for 20 minutes, and the CO2 injection was stopped for 20 minutes. This process was repeated four times. During the CO2 injection and discharge, ethanol was collected through the bottom of the separator. Next, CO2 was vented for 2 hours. After the supercritical drying was completed, the blanket was dried at 150°C and normal pressure for 1 hour to produce a silica aerogel blanket.
[0090] Example 2 A silica aerogel blanket was prepared in the same manner as in Example 1, except that the catalyst composition was mixed so that the total amount of water was 3 equivalents per equivalent of TMES in the catalyst composition. When mixing the catalyst composition, the content of ethanol was also adjusted so that the total content of the catalyst composition was the same, and the base catalyst was 0.64 parts by weight per 100 parts by weight of the total sol.
[0091] Example 3 A silica aerogel blanket was manufactured in the same manner as in Example 1, except that the amount of ammonia water (concentration: 30 wt%) was adjusted and the catalyst composition was mixed so that the base catalyst was 0.48 parts by weight per 100 parts by weight of the total sol.
[0092] Example 4 A silica aerogel blanket was prepared in the same manner as in Example 1, except that the catalyst composition was mixed so that the total amount of water was 2.0 equivalents per equivalent of TMES in the catalyst composition. When mixing the catalyst composition, the content of ethanol was also adjusted so that the total content of the catalyst composition was the same, and the base catalyst was 0.64 parts by weight per 100 parts by weight of the total sol.
[0093] Example 5 A silica aerogel blanket was prepared in the same manner as in Example 1, except that the catalyst composition was mixed so that the total amount of water was 10.0 equivalents per equivalent of TMES in the catalyst composition. When mixing the catalyst composition, the content of ethanol was also adjusted so that the total content of the catalyst composition was the same, and the base catalyst was 0.64 parts by weight per 100 parts by weight of the total sol.
[0094] Comparative Example 1 A silica precursor composition was prepared by adding 31.90 g of prehydrolyzed TEOS (HTEOS), 7.77 g of TMES as a hydrophobizing agent, 47.28 g of ethanol, and 2.80 g of water to a reactor and mixing them. A catalyst composition was prepared by adding 47.28 g of ethanol, 4.22 g of water, and 2.75 g of ammonia water (concentration: 30 wt%) to another reactor and mixing them. A silica aerogel blanket was prepared in the same manner as in Example 1, except that the silica precursor and catalyst composition prepared above were used.
[0095] Comparative Example 2 1.30 mol of ethanol and 0.02 g of acid catalyst HCl were added to a reactor and mixed, and 0.62 mol of hexamethyldisilazane (HMDS) was added and mixed thereto. Then, reflux was performed for 1 hour at 100°C to confirm the generation of ammonia (NH3) gas. One hour after the end of reflux, the reaction solution (catalyst composition) was collected and added to a prehydrolyzed TEOS (HTEOS) ethanol solution (silica content = 20 wt%) and mixed to prepare a silica sol. At this time, the reaction solution is a solution consisting of HMDS, TMES, which is a reaction product of ethanol and acid catalyst, gaseous ammonia (NH3), and ethanol. A silica wet gel blanket was prepared under the same conditions as in Example 1, except that the prepared silica sol was used.
[0096] Comparative Example 3 A silica aerogel blanket was manufactured in the same manner as in Example 1, except that the amount of ammonia water (concentration: 30 wt%) was adjusted and the catalyst composition was mixed so that the base catalyst was 0.26 parts by weight per 100 parts by weight of the total sol.
[0097] Comparative Example 4 The same method as in Example 1 was carried out, except that the amount of ammonia water (concentration: 30 wt%) added was adjusted and the catalyst composition was mixed so that the base catalyst was 1.1 parts by weight per 100 parts by weight of the total sol. However, when the silica precursor composition and the catalyst composition were mixed to prepare a silica sol, the gelation rate was too fast, and before the silica precursor composition and the catalyst composition were uniformly mixed, gelation occurred already, forming a non-uniform gel, and it was not possible to prepare a silica sol. Therefore, it was impossible to impregnate the blanket base material with the silica sol, and it was not possible to prepare a silica aerogel blanket, let alone a fiber composite impregnated with the silica sol.
[0098] (Reference Example 1) A silica precursor composition was prepared by adding 31.90 g of prehydrolyzed TEOS (HTEOS), 24.41 g of ethanol, and 11.12 g of water to a reactor and mixing them. In addition, 60.54 g of ethanol and 0.69 g of ammonia water (concentration: 30 wt%) were added to another reactor and mixed to prepare a catalyst composition. The prepared silica precursor and catalyst composition were mixed to prepare a silica sol, and this silica sol was impregnated into a fiber (glass fiber mat, 10 mm) as a blanket substrate. Gelation was induced for 10 minutes to prepare a silica wet gel blanket. The prepared silica wet gel blanket was aged at a temperature of 50°C for 1 hour using an ammonia (NH3) / ethanol solution (volume ratio of 2.2:97.8). After adding 90% by volume of hexamethyldisilazane (HMDS) / ethanol solution (volume ratio of 5:95) to the aged silica wet gel blanket, surface modification was performed at a temperature of 70° C. for 4 hours. Next, supercritical drying and normal pressure drying were performed under the same conditions as in Example 1 to produce a silica aerogel blanket.
[0099] Experimental Example 1: Gel Time Measurement In the above-mentioned Examples 1 to 5, Comparative Examples 1 to 3, and Reference Example 1, the time required for the gelation reaction of the silica precursor composition over time was measured, and the results are shown in Table 1. Specifically, in each of the Examples, Comparative Examples, and Reference Examples, the catalyst composition was mixed with the silica precursor composition 0.5 hours, 1 hour, and 2 hours after production of the silica precursor composition, and the gelation time was measured, and the difference in gelation time over time after production of the silica precursor composition is shown in Table 1 below.
[0100] [Table 1]
[0101] As shown in Table 1, it can be seen that the gelation time is not affected by the residence time of the silica precursor in Examples 1 to 5 and is maintained at a constant time. Maintaining a constant gelation time can act as a factor for facilitating process control during the manufacture of an aerogel blanket. However, it can be seen that in Comparative Example 1, in which a hydrophobizing agent is included in the silica precursor composition, the gelation time also changes with the change in residence time (elapsed time) after the manufacture of the silica precursor composition, and in such a case, a problem may arise in that it is difficult to apply the process to continuously manufacture an aerogel blanket.
[0102] For example, when a roll-type silica aerogel blanket is manufactured using a roll-to-roll technique, a silica precursor composition and a catalyst composition are stored in a storage tank, and then each composition is sprayed onto a blanket substrate on a conveyer belt, and gelation can be performed while moving the conveyer belt. In this case, if the gelation time differs depending on the residence time of the silica precursor composition in the storage tank, a problem may occur in which gelation does not occur partially in the manufactured wet gel blanket.
[0103] In addition, in the case of Comparative Example 4, the gelation rate was so fast that gelation occurred before the silica precursor and the catalyst composition were uniformly mixed, forming a non-uniform gel, and the gelation time itself could not be measured.
[0104] Experimental example 2: Measurement of physical properties of aerogel blanket 1) Thermal conductivity The thermal conductivity of the silica aerogel blankets prepared in the above examples and comparative examples was measured at room temperature (about 23±3° C.) using a NETZSCH HFM 436 device. The results are shown in Table 2.
[0105] 2) Measurement of water repellency (wt%) The surface water repellency and cross-sectional water repellency of the silica aerogel blankets prepared in the examples and comparative examples were measured.
[0106] Specifically, a 100mm x 100mm test piece (thickness: 10mm) is floated on distilled water at 21±2°C, and the mesh screen on the test piece is submerged 127mm below the water surface. After 15 minutes, the screen is removed, and when the test piece floats up, it is clamped and hung vertically for 60±5 seconds. Next, the weights before and after impregnation are measured, and the weight increase rate is confirmed and expressed as the surface water repellency. The lower the surface water repellency value, the better the hydrophobicity of the silica aerogel blanket surface.
[0107] On the other hand, the cross-sectional water repellency was measured by cutting the 100 mm x 100 mm test piece (thickness: 10 mm) into a 10 mm x 100 mm size and measuring it in the same manner as the surface water repellency. The lower the cross-sectional water repellency value, the better the hydrophobicity of the inside of the silica aerogel blanket.
[0108] [Table 2]
[0109] As shown in Table 2, Examples 1 to 5 show improved or similar levels of thermal conductivity compared to Comparative Examples 1 to 3 and Reference Example 1 prepared by a conventional method. This confirms that aerogel blankets with good thermal insulation performance can be prepared in Examples 1 to 5.
[0110] In addition, it can be confirmed that Examples 1 to 5 have significantly lower values of surface water repellency and cross-sectional water repellency than Comparative Examples 1 to 3, and in particular, it can be confirmed that the cross-sectional water repellency of Examples 1 to 3 is significantly lower than that of Reference Example 1. From the excellent cross-sectional water repellency properties of Examples 1 to 3, it can be confirmed that aerogel is uniformly formed not only on the surface of the blanket but also inside the blanket. In addition, it can be confirmed that Comparative Examples 2 and 3 have surface water repellency and cross-sectional water repellency values of 10 wt% or more, and hydrophobicity is not expressed at all. In Comparative Examples 2 and 3, aging and surface modification are not performed even when left under room temperature conditions, so a hydrophobic aerogel blanket is not formed.
[0111] In addition, in Comparative Example 4, it was impossible to impregnate the blanket base material with silica sol, and it was not possible to produce a silica aerogel blanket, let alone a fiber composite impregnated with silica sol. Therefore, it was not possible to measure the thermal conductivity and water repellency themselves.
[0112] Meanwhile, in the case of Reference Example 1, when wet aging and surface modification were performed at high temperatures for a predetermined time according to the conventional method without leaving it at room temperature, it was confirmed that a normal hydrophobic silica aerogel blanket was formed, but the energy consumption for wet aging and surface modification was larger than that of the Examples, and an excessive amount of solvent was used during the process, resulting in a large loss of the solvent.In addition, since a separate surface modification supplying device, aging solution supplying device, etc. must be further provided, not only are there inconveniences in the process, but there is also a problem of a significant increase in manufacturing costs.
[0113] In contrast, in Examples 1 to 5, gelation, aging, and surface modification can all be achieved simply by leaving the mixture at room temperature, which allows for a significant reduction in energy consumption. In addition, the amount of solvent used can be reduced because the solvent can be easily reused. In addition, the aerogel blanket can be produced using relatively simple equipment.
[0114] The above description of the present invention is for illustrative purposes only, and those skilled in the art will understand that the present invention can be easily modified into other specific forms without changing the technical concept or essential features of the present invention. Therefore, the above-described embodiments should be understood to be illustrative in all respects and not limiting.
Claims
[Claim 1] A blanket substrate and a silica aerogel formed inside and on a surface of the blanket substrate, The surface water repellency is 2.18 wt% to 6.85 wt%, The cross-sectional water repellency is 0 wt% to 7 wt%, The surface water repellency is determined by floating a silica aerogel blanket test piece having a size of 100 mm x 100 mm (thickness 10 mm) on distilled water at 21 ± 2°C, submerging the mesh screen on the test piece to 127 mm below the water surface, removing the screen after 15 minutes, and when the test piece floats up, clamping the test piece and hanging it vertically for 60 ± 5 seconds, and then measuring the weight of the test piece before and after the immersion, and determining the weight increase rate. The cross-sectional water repellency is determined by cutting a 100 mm x 100 mm (thickness 10 mm) silica aerogel blanket in the thickness direction to a size of 10 mm x 100 mm (thickness 10 mm), floating the obtained test piece on distilled water at 21 ± 2 ° C., submerging the mesh screen on the test piece to 127 mm below the water surface, removing the screen after 15 minutes, and when the test piece floats up, clamping the test piece with a clamp and hanging it vertically for 60 ± 5 seconds, and then measuring the weight of the test piece before and after impregnation, and confirming the weight increase rate of the silica aerogel blanket.
Citation Information
Patent Citations
Improved hydrophobic airgel materials
JP2017533163A
Manufacturing method of hydrophobic silica aerogel and hydrophobic silica aerogel manufactured therefrom
KR101147494B1